Personalizing HRI in Musical Instrument Practicing: The Influence of Robot Roles (Evaluative Versus Nonevaluative) on the Child’s Motivation for Children in Different Learning Stages - Song, Heqiu; Barakova, Emilia I.; Markopoulos, Panos; Ham, Jaap (Frontiers in Robotics and AI, 2021)
Learning to play a musical instrument involves skill learning and requires long-term practicing to reach expert levels. Research has already proven that the assistance of a robot can improve children’s motivation and performance during practice. In an earlier study, we showed that the specific role (evaluative role versus non-evaluative role) the robot plays can determine children’s motivation and performance. In the current research, we argue that the role of the robot has to be different for children in different learning stages (musical instrument expertise levels). Therefore, this study investigated whether children in different learning stages would have higher motivation when assisted by a robot in a different supporting role (i.e., evaluative role versus non-evaluative role). We conducted an empirical study in a real practice room of a music school with 31 children who were at different learning stages (i.e., beginners, developing players, and advanced players). In this study, every child practiced for three sessions: practicing alone, assisted by the evaluative robot, or assisted by the non-evaluative robot (in random order). We measured motivation by using a questionnaire and analyzing video data. Results showed a significant interaction between condition (i.e., alone, evaluative robot, and non-evaluative robot) and learning stage groups indicating that children in different learning stage groups had different levels of motivation when practicing alone, or with evaluative or non-evaluative robot. More specifically, beginners had higher persistence when practicing with the non-evaluative robot, while advanced players expressed higher motivation after practicing with a robot than alone, but no difference was found between the two robot roles. Exploratory results also indicated that gender might have an interaction effect with the robot roles on child’s motivation in music practice with social robots. This study offers more insight into child-robot interaction and robot role design in musical instrument learning. Specifically, our findings shed light on personalization in HRI, that is, adapting the role of the robot to the characteristics and the development level of the user.